Numerical Stability Analysis of the Dam Foundation Under Complex Geological Conditions at Great Depth: A Case Study of Kala Hydropower Station, China - Li, Wei; Wu, Weiwei; Zhang, Jiuchang (Frontiers in Physics, 2022)
The stability of dam foundations at great depth has always been a challenging problem concerned by designers. This study built a 3D numerical model of the dam and foundation under a complex geological condition in the project area of the Chinese Kala hydropower station. The numerical model was imported into the finite difference software FLAC3D to conduct a numerical simulation. Overload and strength reduction methods were adopted to evaluate the stability of the dam foundation at great depth. The results indicated that the structural faults had an essential impact on the stability of the dam foundation. The stability analysis showed that the safety factor of the dam foundation is greater than 2.5, which met the standard's requirements. The simulation results can provide a reference for the design and engineering reinforcement of the Kala dam foundation.